Analisis Performansi Jaringan 4G Telkomsel Menggunakan Metode Drive Test - Muhammad Harun Ashar; Dinda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Availability and quality of the network is very important considering the needs of people who are all connected to internet services. Kuma Hamlet, which is in Sarudu District, West Celebes, has gained access to the 4G service network through the Telkomsel operator, but problems still occur such as a slow network or weak network connection. This study aims to analyze the performance of the Telkomsel 4G network in Dusun Kuma using the Drive Test Method. The research results obtained were Telkomsel's 4G network performance results using the Drive Test Method in Kuma hamlet carried out at 15 Location Points with the help of the Gnet Track Pro Application which were obtained at 3.0 (Normal), with Maximum Performance reaching 4.0 (Good), and Minimum Performance reaching 2.3 (Bad).